1993
DOI: 10.1111/j.1471-4159.1993.tb03205.x
|View full text |Cite
|
Sign up to set email alerts
|

GT1b Ganglioside Prevents Tetanus Toxin‐Induced Protein Kinase C Activation and Down‐Regulation in the Neonatal Brain In Vivo

Abstract: A single dose of 0.25 ng of tetanus toxin (TeTx), equivalent to -5 minimal lethal doses, injected intracerebrally to I -day-old rats, caused translocation, i.e., activation, of Ca'+-phosphatidylsenne-dependent protein kinase C (PKC) from the cytosolic to the membrane compartment within 1 h. Six hours after treatment with the toxin, a 40-50% reduction in the total brain PKC (cytosolic plus membrane) activity was noticed. G T l b (2 pg per brain) ganglioside, a putative receptor for TeTx, completely prevented en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…This may be explained by the reversible nature of the interaction between the TeTx and specific binding sites on the cell plasma mcmbranc (Yavin Ct al., 1981). Whether gangliosides may serve as receptors for this interaction, as previously suggested (Aguilera et al, , 1993, remains to be studied. These data are analogous to other bacterial toxin-derived enzymatic activities (Shoshan et al, 1993) and growth factors such as interleukin-3, which stimulate a rapid and transient increase in the redistribution of PKC activity from the cytosol to the membrane (Farrar et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be explained by the reversible nature of the interaction between the TeTx and specific binding sites on the cell plasma mcmbranc (Yavin Ct al., 1981). Whether gangliosides may serve as receptors for this interaction, as previously suggested (Aguilera et al, , 1993, remains to be studied. These data are analogous to other bacterial toxin-derived enzymatic activities (Shoshan et al, 1993) and growth factors such as interleukin-3, which stimulate a rapid and transient increase in the redistribution of PKC activity from the cytosol to the membrane (Farrar et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…The latter mechanism is concurrent with our previous in vivo studies, showing activity translocation of Ca21iphosphatidylserine (Ca2~i PtdSer)-dependent protein kinase C (PKC) followed by down-regulation after intracerebral injection of TeTx in adult and immature rats . PKC translocation appeared before the classic symptoms of tetanus neurotoxicity in the perinatal rat (Aguilera et al, 1993). TeTx produces in vivo intoxication via a complex sequence of biochemical reactions, of which the Zn2t dependent metalloprotease activity probably represents the hallmark of its neurolethal action (Montecucco and Schiavo, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Later, our group described activation and subsequent down-regulation of PKC after intracerebral injection of TeTx into adult and neonatal rat brain [9]. PKC translocation appeared before the classic symptoms of tetanus neurotoxicity in the perinatal rat [10]. The increase in polyphosphoinositide hydrolysis in rat cerebral cortex preparations treated with TeTx indicates activation of phospholipases, an effect directly related to PKC activation [11].…”
Section: Introductionmentioning
confidence: 99%
“…Signaling cascades are activated as a prelude to classical tetanus symptoms [195,196]. Gil et al further demonstrated activation of Trk receptors by H C T and TeNT, which trigger the activation of Akt and ERK1/2 in cultured cortical neurons [192].…”
Section: Cnt and Nt Signalingmentioning
confidence: 98%